EXPLORING THE IMPACT OF CLIMATE CHANGE ON PAKISTANI WOMEN’S MENTAL HEALTH - Niaz, Unaiza (Journal of Pakistan Psychiatric Society, 2024)
Climate change is a multifaceted threat to global public health that is disproportionately affecting vulnerable populations such as women in Pakistan. This article explores the gender-specific mental health consequences of climate change by highlighting how socioeconomic inequities, maternal vulnerabilities, limited healthcare infrastructure, and socio-political instability exacerbate the crisis. It emphasises the urgent need for integrated, gender-sensitive, and mental health–inclusive climate policies and also advocates for increased investment, stigma reduction, and grassroots psychosocial interventions to empower women as both recipients and providers of care. The article further aims to prompt critical dialogue and action among researchers, policymakers, and healthcare professionals for Pakistan to transform its climate response into a medium for mental health reform, gender equity, and societal resilience.